An Experimental Verification of a Methodology for Assessing The Energy Performance on Turning Processes - Sri Raharno; Yatna Yuwana Martawirya; Jeffry Aditya Cipta Wijaya (Mesin, 2016)
This paper aimed to experimentally verify the methodology for assessing energy performance of turning processes that had been developed on the prior research. Specific energy consumption is used as the indicator in the process assessment. The experimental verification can be separated into two main steps. The first step is to construct the reference values of specific energy consumption and the second step is to compare the reference values to the specific energy consumption from the assessed process. The reference values were constructed based on the data of specific energy (from experiment) using data envelopment analysis (DEA) method. In this case, MaxDEA Basic 6.6 program has been used to determine the reference values. The experiment was conducted using several lathe machines based on the certain metering strategy. The metering strategy must be determined to maintain the consistency and validity of the process assessment.  After the reference values were constructed, the assessment can be carried out. Energy consumption from the assessed process was measured using power analyzer, and then it was converted into specific energy consumption value according to the material removal rate. Energy reduction score could be calculated based on the distance between the data of specific energy consumption (from the assessed process) and the reference value. The energy performance of the machine is better if the score of energy reduction is lower and nearer to the reference value. The methodology was designed to be as simple as possible in order to be appropriately implemented on the industry, but without reduce the quality of the assessment. shedding.